Considering biodiversity in food purchases: consumer wishes and communication strategies - Böhm, Uta; Schäfer, Martina (Frontiers in Sustainable Food Systems, 2025)
Research on sustainable consumer behavior when purchasing food so far has mainly focused on organic products as well as on local and climate-friendly options and on minimizing packaging. Biodiversity protection—an increasingly urgent concern due to its global decline—has received little attention in this context. There is hardly any research available on the knowledge and attitudes consumers have regarding the protection of biodiversity, to what extent they are prepared to adapt their purchasing behavior accordingly and how companies can successfully communicate biodiversity protection measures to consumers. This article addresses this gap. Drawing on findings from two representative consumer surveys conducted in Germany in 2022 (n = 1,028) and 2023 (n = 1,500), it highlights the importance consumers place on food produced with biodiversity-friendly practices. The article identifies consumer groups who are particularly interested in this issue and discusses how information on product packaging can raise awareness of biodiversity protection. The results of a conjoint analysis suggest that strategic communication on product packaging—such as indicating a positive biodiversity value or using an appealing slogan—can enhance consumers’ willingness to purchase and pay higher prices for biodiversity-friendly food products.